Writing is the foundation of the educational institution in ancient Iraq - Ismail, Prof. Dr. Shaker Mahmoud Ismail (Sulaimani Journal for Humanities, 2026)
Writing is one of the most prominent civilizational achievements in human history throughout the ages. It has moved man from the stage of darkness to the stage of light, and its importance has surpassed all other civilizational achievements, ancient and modern. Therefore, its invention became the beginning of human history, and thus it is considered a dividing line between the two most important eras. In human history, prehistoric (stone ages) and historical eras. Based on the above, writing is the first step in the educational institutional building in ancient Iraq, and even in modern times. Writing is the origin of science and all sciences, and based on this great importance, we have made it the title of our humble research (Writing is the origin of the educational institution in ancient Iraq). Trying to clarify the stages of the invention of writing and its types, as well as knowing how ancient races learned to write in those times. The research will be divided into a number of topics, the first of which will be about the cultural discoveries that paved the way for writing. We will discuss the appearance of seals and their types and show their impact on the invention of writing. Then we will discuss the stages that writing went through in ancient Iraq. We will then discuss the methods of learning that were practiced by the Iraqis, and the schools that were These students learn in it, as it is the main place from which the institutional structure began, which later expanded to include all aspects of writing in various daily life.
Keywords: writing; educational institution; ancient Iraq